(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Ensuring the quality of foreign language teaching of younger generation, radically improving the system of training specialists fluent in foreign languages, training of qualified personnel who meet international educational standards through the acquisition of foreign languages is one of the goals of education reform.